The Goursat problem for hyperbolic linear third order equations - Korzyuk, V. I. (Mathematical Modelling and Analysis, 2001)
The third order hyperbolic linear differential equation is considered in the non‐cylindrical domain of multidimensional Euclidean space. The equation operator is a composition of a differentiation operator of the first order and second order operator, which is hyperbolic with respect to the prescribed vector field. Apart from the equation, Goursat and Cauchy conditions are defined for an unknown function. Thus the boundary of the domain, where this hyperbolic equation is defined, consists of characteristic hypersurfaces, the hypersur‐faces, where Cauchy conditions are prescribed, and hypersurfaces with no conditions. For the mentioned problem the existence and uniqueness of the strong solution are proved using mollifying operators with a variable step and functional analysis methods on the base of the previously proved energy inequality. Trečios eilės tiesinių hiperbolinių lygčių Goursat uždavinys Santrauka. Daugiamatė Euklido erdvės necilindrinėje srityje nagrinėjama trečios eilės tiesinė hiperbolinė lygtis. Lygties operatorius yra pirmos eilės diferencialinio operatoriaus ir antros eilės operatoriaus, kuris yra hiperbolinis apibrėžto vektorinio lauko atžvilgiu, kompozicija. Srities kontūrą sudaro charakteristinis hiperpaviršius (jame formuojama Goursat sąlyga), hiperpaviršiaus, kuriame formuluojama Caushy salyga, ir laisvas nuo bet kokių salygų hiperpaviršius. Naudojantis kintamojo žingsnio suvidurkinto operatoriaus bei funkcines analizės metodais, paremtais energetine nelygybe, įrodytas šio uždavinio stipriojo sprendinio egzistavimas ir vienatis. First Published online: 14 Oct 2010